2019
DOI: 10.1371/journal.pbio.3000436
|View full text |Cite
|
Sign up to set email alerts
|

Peptide presentation by bat MHC class I provides new insight into the antiviral immunity of bats

Abstract: Bats harbor many zoonotic viruses, including highly pathogenic viruses of humans and other mammals, but they are typically asymptomatic in bats. To further understand the antiviral immunity of bats, we screened and identified a series of bat major histocompatibility complex (MHC) I Ptal-N*01:01–binding peptides derived from four different bat-borne viruses, i.e., Hendra virus (HeV), Ebola virus (EBOV), Middle East respiratory syndrome coronavirus (MERS-CoV), and H17N10 influenza-like virus. The structures of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 58 publications
1
37
0
1
Order By: Relevance
“…Different mammals have diverse MHC gene repertoires and thus present distinct antigens. In particular, recent data from various bat species indicated that many MHC class I molecules have a 3-or 5-amino acid insertion in the peptide binding pocket, resulting in very different presented peptide repertoires compared to the MHC class I molecules of other mammals (Abduriyim et al, 2019;Lu, Dan AND Liu, 13 Kefang AND Zhang, Di AND Yue, Can AND Lu, Qiong AND Cheng, Hao AND Wang, Liang AND Chai, Yan AND Qi, Jianxun AND Wang, Lin-Fa AND Gao, George F. AND Liu,William J., 2019;Ng et al, 2016;Papenfuss et al, 2012;Wynne et al, 2016) . Thus, the selective pressure acting on T cell epitopes is most likely volatile and not conserved in humans and bats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mammals have diverse MHC gene repertoires and thus present distinct antigens. In particular, recent data from various bat species indicated that many MHC class I molecules have a 3-or 5-amino acid insertion in the peptide binding pocket, resulting in very different presented peptide repertoires compared to the MHC class I molecules of other mammals (Abduriyim et al, 2019;Lu, Dan AND Liu, 13 Kefang AND Zhang, Di AND Yue, Can AND Lu, Qiong AND Cheng, Hao AND Wang, Liang AND Chai, Yan AND Qi, Jianxun AND Wang, Lin-Fa AND Gao, George F. AND Liu,William J., 2019;Ng et al, 2016;Papenfuss et al, 2012;Wynne et al, 2016) . Thus, the selective pressure acting on T cell epitopes is most likely volatile and not conserved in humans and bats.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all these viruses, with the exclusion of SARS-CoV, were sampled from bats. Thus, whereas structural/functional constraints are expected to be maintained across long evolutionary time frames, the pressure exerted by the human cell-mediated immune response is not, as, in different species, antigen processing within host cells results in the preferential presentation of diverse viral epitopes to T lymphocytes depending on the MHC gene repertoire and on distinct preferences of the antigen processing pathway (Abduriyim et al, 2019;Burgevin et al, 2008;Hammer et al, 2007; Lu, Dan AND Liu, Kefang AND Zhang, Di AND Yue, Can AND Lu, Qiong AND Cheng, Hao AND Wang, Liang AND Chai, Yan AND Qi, Jianxun AND Wang, Lin-Fa AND Gao, George F. AND Liu,William J., 2019;Wynne et al, 2016). Conversely, epitopes for antibodies tend to be conserved across species (Tse et al, 2017;Wiehe et al, 2014) and consequently the selective pressure acting on these positions is expected to be constant across time and hosts.…”
Section: Antigenic Variability Of Sars-cov-2 Proteinsmentioning
confidence: 99%
“…devil MHC-I allele SahaI*27 against the recently described bat MHC-I structure (Ptal-N*01-01)(15), shows a high level of conservation within the F pocket that is absent in the B pocket and likely explains the different binding properties of the devil MHC-I molecules. Interestingly, analysis of all MHC-I alleles expressed by the tumour and host cell lines predicts a B-pocket preference for only SahaI*27 and SahaI*74/88 (which differ by only one amino acid across the a1 and a2 domains), but a F-pocket prediction for a hydrophobic residue is largely consistent across the alleles.…”
mentioning
confidence: 84%
“…In devils, three polymorphic classical MHC-I genes (Saha-UA, -UB and -UC) and three nonclassical genes (Saha-UD, -UK and -UM) have been identified, however very little is known about their function or the nature of their ligands (14). Indeed, outside of well characterised species such as human and mouse and those of agricultural importance there has been little analysis of MHC peptide binding in wild species (with a notable exception of the bat MHC (15)(16)(17)). DFT1 cells express low levels of MHC-I, explaining the lack of rejection by CD8 + -T cells (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation